2001
DOI: 10.1109/20.911846
|View full text |Cite
|
Sign up to set email alerts
|

Active magnetic bearings for energy storage systems for combat vehicles

Abstract: Abstract--To minimize CHPS flywheel size and mass, a topology was chosen in which the rotating portion of the flywheel is located outside the stationary components. Accordingly, magnetic bearing actuators are required which share this "inside-out" configuration. Because of inherent low loss and nearly linear force characteristics, UT-CEM has designed and analyzed permanent magnet bias bearing actuators for this application. To verify actuator performance, a non-rotating bearing test fixture was designed and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…With these design choices, combined with the amount of energy to be stored in the flywheel, the following approach can be used to dimension the machine. The homopolar flux density B f 0 is calculated from B max andB f 1 for a square rotor in (8). The minimum airgap flux density (9), the required field winding ampereturns (10), the axial length needed for the field winding (11), and the maximum airgap length (12) can then be calculated.…”
Section: Ac Homopolar Motor Sizingmentioning
confidence: 99%
See 1 more Smart Citation
“…With these design choices, combined with the amount of energy to be stored in the flywheel, the following approach can be used to dimension the machine. The homopolar flux density B f 0 is calculated from B max andB f 1 for a square rotor in (8). The minimum airgap flux density (9), the required field winding ampereturns (10), the axial length needed for the field winding (11), and the maximum airgap length (12) can then be calculated.…”
Section: Ac Homopolar Motor Sizingmentioning
confidence: 99%
“…Previous work has concluded that bearing loss can be substantially reduced by using carefully designed magnetic bearings [8] and that frictional windage loss can be nearly eliminated by using a vacuum of approximately 1mTorr [9]. The magnetic losses associated with the motor depend on the type of motor chosen.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advantages of high speed, no friction, high precision and long service life [1][2][3][4][5], magnetic bearings play an important role in electric drives working under high speed, vacuum and clean conditions. They have been applied in rotating machinery applications like motorized spindles, agile satellites and flywheel systems [6][7][8][9][10][11][12]. The most common configurations for radial magnetic bearings are eight-pole type and four-pole type [13].…”
Section: Introductionmentioning
confidence: 99%
“…Along with vertical lifting capability, the lateral stiffness affects dynamic performance and may limit operation. For applications such as flywheel energy storage, operation above critical speed may be required to meet energy storage requirements [4]. The low lateral stiffness and damping capabilities of HTSC bearings have been shown to impede operations above critical speeds [5].…”
Section: Introductionmentioning
confidence: 99%